Synthesis of magnetic basic palm kernel shell catalyst for biodiesel production and characterisation and optimisation by Taguchi method - Celine, Ming Hui Goh; Yie, Hua Tan; Mubarak, N. M.; Kansedo, Jibrail; Rashid, Umer; Khalid, Mohammad; Walvekar, Rashmi Gangasa (Springer, 2021)
This paper illustrated the latest breakthroughs which involved the use of eco-friendly and recyclable magnetic palm kernel shell-derived catalysts (Fe-PKS and Fe-KOH-PKS) for methanolysis of palm oil to produce iodiesel. The magnetic catalyst is obtained from abundant carbon-based biomass, i.e. waste palm kernel shell using pyrolysis. Characterisation of the catalyst with field-emission Scanning Electron microscopy (FESEM), energy-dispersive X-Ray spectroscopy (EDX), Brunauer–Emmett–Teller (BET), vibrating sample magnetometer (VSM), temperature-programmed desorption of CO2 (TPD-CO2) thermogravimetric analysis (TGA) and Fourier-transform infrared spectroscopy (FTIR) analysis was conducted to correlate the catalyst characteristic with transesterification activity. The presence of KOH in the catalyst has beneficial effects on the catalyst performance in transesterification. Next, the L-9 orthogonal set-up of experimental factors established by the Taguchi method was employed to determine the optimal operating conditions for Fe-KOH-PKS catalyst. The highest biodiesel yield of 99.43% using Fe-KOH-PKS catalyst was achieved with optimal operating conditions of 7.5 wt% catalyst loading, 9:1 methanol to oil ratio at 65 °C after 2 h. The catalyst was reused for four cycles, with the final run of biodiesel yield of 70.1%. This reflects the synthesised magnetic waste catalyst from palm kernel shell has demonstrated satisfied reusability and good stability in producing biodiesel.